2011
DOI: 10.3174/ajnr.a2842
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Thromboemboli Histology on the Performance of a Mechanical Thrombectomy Device

Abstract: BACKGROUND AND PURPOSE:Recently we published a novel method of thrombus preparation for use in a swine model for evaluation of thrombectomy designs. The clot (fibrin rich clot) is characterized by its similarity in histologic characteristics to the thromboemboli recovered from stroke patients. The purpose of this latest study was to evaluate if the performance of a mechanical thrombectomy device was affected by the histologic characteristics of thromboembolus. Erythrocyte rich clot, which was created using exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 14 publications
3
110
1
4
Order By: Relevance
“…13 Recently, several investigators reported the results of histologic studies analyzing the composition of the clots retrieved by mechanical thrombectomy in patients with acute ischemic stroke. 6,[14][15][16] These studies demonstrated that the presence of an SVS on GRE imaging was notably associated with a higher red blood cell content in the clots, whereas an absence of SVS was associated with fibrin-rich clots. Fibrin-dominant clots are usually formed because of injury to the endothelium overlying the complicated atheromatous plaque.…”
Section: Discussionmentioning
confidence: 87%
“…13 Recently, several investigators reported the results of histologic studies analyzing the composition of the clots retrieved by mechanical thrombectomy in patients with acute ischemic stroke. 6,[14][15][16] These studies demonstrated that the presence of an SVS on GRE imaging was notably associated with a higher red blood cell content in the clots, whereas an absence of SVS was associated with fibrin-rich clots. Fibrin-dominant clots are usually formed because of injury to the endothelium overlying the complicated atheromatous plaque.…”
Section: Discussionmentioning
confidence: 87%
“…Recent in vitro data seem to suggest that fibrin‐rich thrombi containing relatively low amounts of erythrocytes are more resistant to thrombectomy, possibly because of their frictional properties 22, 23…”
Section: Discussionmentioning
confidence: 99%
“…Other areas of interest would include analysis of the retrieved and injected clot, including variations of the clot production, such as the use of fibrin-rich clot. 19 Analysis of distal clot propagation and time to recanalization of bifurcation occlusions may also be of interest in future studies.…”
Section: Future Experimentsmentioning
confidence: 99%